PENGARUH VARIASI KONSENTRASI EKOENZIM DAN GULA MERAH PADA PERTUMBUHAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Fitriani Fitriani; Najla Lubis; Sri Mahareni Br. Sitepu (Agros Journal of Agriculture Science, 2023)
This study aims to determine the effectiveness of using different doses of eco-enzymes in the cultivation of white oyster mushrooms (Pleurotus ostreatus), knowing the effectiveness of using different doses of brown sugar in the cultivation of white oyster mushrooms  .  White oyster mushrooms require nutritional supplements during their growing years. Additional nutrients can be obtained using water-soluble ecoenzymes and fertilizing the substrate of white oyster mushrooms. Ecoenzyme nutrients and brown sugar can increase the yield and growth of white oyster mushrooms at harvest time. This study used factorial complete randomized design (RAL) with 2 factors, 16 treatments, 3 repeats, and 48 baglogs. G0 = 0%/baglog, G1 = 40%/baglog, G2 = 80%/baglog, G3 = 120%/baglog. Factor Pertreatment 2 Using eco enzyme with symbol "E" E0 = 0%/baglog, E1 = 20%/baglog, E2 = 40%/baglog, E3 = 60%/baglog. The highest mycelium growth data is found at G0 with a height of 28.83 cm.The highest height of the mushroom  stalk is E0 with a height of 3.93 cm. The largest hood diameter is found in the E1 treatment with a diameter of 7.68 cm. The highest number of saplings is E3 with 7.50 saplings. The highest wet weight was found in the G3 treatment with the highest wet weight of 109.00 g. The data obtained were analyzed with ANOVA. The results of the variation analysis continued with the Duncan distance test. The results showed that the growth height of the mushroom mycelium, the number of branches, the thickness of the cap, the height of the mushroom and the diameter of the cap on the interaction of brown sugar intake and ecological enzymes in white oyster mushrooms gave the following results: Results did not differ markedly, but wet weight yields did not differ markedly. The results differed significantly.Keywords: ecoenzymes, brown sugar, oyster mushrooms  INTISARIPenelitian ini bertujuan untuk mengetahui efektivitas penggunaan konsentrasi ekoenzim yang bervariasi pada budidaya jamur tiram putih (Pleurotus ostreatus), dan mengetahui efektivitas penggunaan konsentrasi gula merah bervariasi pada budidaya jamur tiram putih. Jamur tiram putih memerlukan suplemen nutrisi selama pertumbuhannya. Nutrisi tambahan diperoleh dengan menggunakan ekoenzim yang larut dalam air dan pemupukan substrat jamur tiram. Nutrisi ekoenzim dan gula merah dapat meningkatkan hasil dan pertumbuhan jamur tiram pada saat panen. Penelitian ini menggunakan rancangan acak lengkap faktorial (RAL) dengan 2 faktor, 16 perlakuan, 3 ulangan, dan 48 baglog. Faktor perlakuan 1 gula merah disimbolkan dengan G0 = 0%/baglog, G1 =  40%/baglog, G2 = 80%/baglog, G3 = 120%/baglog. Faktor Perlakuan 2 ekoenzim dengan simbol E0 = 0%/baglog, E1 = 20%/baglog, E2 = 40%/baglog, E3 = 60%/baglog. Hasil penelitian menunjukkan bahwa data pertumbuhan miselium tertinggi terdapat pada G0 yaitu 28,83 cm, tinggi tangkai jamur tertinggi adalah E0 yaitu 3,93 cm, diameter tudung terbesar pada E1 yaitu 7,68 cm, jumlah anakan terbanyak adalah E3 yaitu 7,50 anakan. Berat basah tertinggi pada G3 yaitu 109,00 g. Data yang diperoleh dianalisis dengan ANOVA, dan dilanjutkan dengan uji jarak Duncan. Hasil penelitian menunjukkan bahwa tinggi pertumbuhan miselium jamur, jumlah cabang, tebal tutup, tinggi badan jamur dan diameter tutup pada interaksi asupan gula merah dan ekoenzim pada jamur tiram putih memberikan hasil tidak berbeda nyata, namun hasil berat basah  berbeda sangat nyata. Hasilnya berbeda secara signifikan.Kata kunci: ekoenzim, gula merah, jamur tiram